Midwifery Students Fear of Delivery Process - Neslihan Keser Ozcan; Nur Elcin Boyacıoglu; Neriman Guducu; Seda Goncu Serhatlıoglu; Emine Yıldırım; Medine Koc; Fadime Bingol (Journal of Caring Sciences, 2019)
Introduction: To determine the fields related to delivering babies in which students experience the most fear. Methods: A descriptive/cross-sectional study was performed between September and October 2017. The population of the study consisted of students receiving midwifery education in Turkey, and the sample consisted of students from six universities studying in the third and fourth years of a midwifery program. Data were collected from 732 midwifery students selected with the purposeful maximum variation sampling method. The study measured data collected with a questionnaire entitled "Midwives’ Fear of Delivery Process." Results: In general, students are more afraid of practices with which they say they have more experience (practices related to episiotomy and vaginal palpation), and they are less afraid of practices (interventional) (such as cord prolapse, ablatio placenta, placenta previa) with which they have less experience or no experience at all and of cases in which they can get hurt. The students feel most sufficient when performing prenatal and postnatal practices and feel insufficient when it comes to practices during delivery. Conclusions: Interestingly, students are afraid of the fields that they say they have practiced most (such as vaginal palpation). Before clinical practice, instructors can determine students’ fears and deficiencies in relation to procedures and areas of practice and can develop approaches for alleviating their fears and weaknesses.